Daya Pintal dan Kekuatan Benang Bulu Domba Priangan dan Peranakan Merino - M Duldjaman; T R Wiradarya; M.I H Muttaqin (Media Peternakan, 2006)
Priangan sheep is a native sheep of Indonesia and considered as a hair sheep. Its main product is meat. Recently, the Priangan sheep is crossed with a Merino sheep to produce the Priangan-Merino crossbred. Since the Merino sheep is considered as a wool sheep, it is expected that the Priangan-Merino sheep will have a better quality of wool than the Priangan sheep. To measure the wool improvement of the Priangan-Merino crossbred, an experiment was conducted. Fifteen Priangan sheeps and 15 Merino crossbreds were used in this experiment. The spinning count and wool yarn staple length were measured. The experimental statistics and the design of the experiment was completely ramdomized design. The results indicated that staple strength of wool yarn of Priangan was not significantly different with that of Merino cross. Spinning count was significantly different (P < 0.01) between breed. Key words : Yarn, Priangan and Merino cross, staple strenght, spinning count